The long-term impact of biogenic volatile organic compound emissions on urban ozone patterns over central Europe: contributions from urban and rural vegetation - M. Liaskoni; P. Huszár; L. Bartík; A. P. Prieto Perez; J. Karlický; K. Šindelářová (Atmospheric Chemistry and Physics)
The paper evaluates the long-term (2007–2016) impact of biogenic volatile organic compound (BVOC) emissions on urban ozone patterns over central Europe, specifically focusing on the contribution of urban vegetation using a regional climate model coupled offline to a chemistry transport model. BVOCs are emitted by terrestrial ecosystems, and their impact is considered especially important over NOx-rich environments such as urban areas. The study evaluates the impact of BVOC emissions on ozone (O3), formaldehyde (HCHO), and hydroxyl radical (OH) near-surface concentrations, showing an increase in summer ozone by 6 %–10 % over large areas in central Europe due to their emissions. It also demonstrates a substantial increase in formaldehyde concentrations. Additionally, the impact of BVOC emissions on hydroxyl radical concentrations shows a decrease over most of the modeled region by 20 %–60 %, with some increases over urban areas. Impacts on peroxy radicals (HO2 and higher RO2) are shown too.